Barrett's esophagus current approaches to diagnosis and management - Gençosmanoglu, Rasim; Kalayci, Cem (My University, 2001)
Since its first description, the definition of Barrett's esophagus (BE) has evolved from the macroscopic visualization of gastric-appearing mucosa in the esophagus to the histologic identification of goblet cells confirming the presence of intestinal metaplasia within the esophagus. BE develops as a consequence of chronic mucosal injury in patients with long- lasting gastroesophageal reflux disease. The clinical significance of BE is that it is the only known risk factor for esophageal adenocarcinoma. Endoscopy and biopsy is necessary for the diagnosis of BE as well as for observing the development of dysplasia. The optimal treatment for Barrett's metaplasia and dysplasia is still being debated. Neither aggressive medical acid suppression nor antireflux surgery can induce a predictable regression of BE or exert a protective effect against its malignant degeneration. There is no consensus on a particular guideline for endoscopic surveillance with the means of repeating period and biopsy protocol. In the presence of low-grade dysplasia, endoscopic ablation modalities including multipolar electrocautery, argon plasma coagulation, endoscopic mucosal resection, heater probe, a variety of lasers, cryotherapy and photodynamic therapy should be subjected. Cancer can occur under the re-epitheliazed mucosa following ablation. None of these approaches can obviate the need for continued endoscopic surveillance. Since patients with high-grade dysplasia are at high risk for having a focus of adenocarcinoma, esophagectomy should be indicated to those who are medically fit.
Keywords: Barrett's esophagus, Gastroesophageal reflux, Endoscopy, Dysplasia, Esophageal cancer, Endoscopic ablation, Esophagectomy.